2013
DOI: 10.2337/db11-0785
|View full text |Cite
|
Sign up to set email alerts
|

Gliotransmission and Brain Glucose Sensing

Abstract: Hypothalamic glucose sensing is involved in the control of feeding behavior and peripheral glucose homeostasis, and glial cells are suggested to play an important role in this process. Diazepam-binding inhibitor (DBI) and its processing product the octadecaneuropeptide (ODN), collectively named endozepines, are secreted by astroglia, and ODN is a potent anorexigenic factor. Therefore, we investigated the involvement of endozepines in brain glucose sensing. First, we showed that intracerebroventricular administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
114
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(124 citation statements)
references
References 43 publications
8
114
0
2
Order By: Relevance
“…These findings are in line with growing literature showing that hypothalamic glial cells are involved in central glucose sensing and action (25)(26)(27)(28)(29). It is important to mention that we did not observe an increase in palmitate oxidation in response to AICAR in cortical astrocytes.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These findings are in line with growing literature showing that hypothalamic glial cells are involved in central glucose sensing and action (25)(26)(27)(28)(29). It is important to mention that we did not observe an increase in palmitate oxidation in response to AICAR in cortical astrocytes.…”
Section: Discussionsupporting
confidence: 80%
“…Hypothalamic neurons (24) and glia (25)(26)(27)(28)(29) are both able to sense glucose, and the importance of astroglia in central nutrient sensing has been recently emphasized (30). It is unclear if glucose modulation of LCFACoA metabolism occurs in neurons and/or astrocytes and whether or not such a feature distinguishes hypothalamic nuclei from other brain regions.…”
mentioning
confidence: 99%
“…In addition, icv injection of ODN increases POMC mRNA level and decreases NPY mRNA level in the AN of the hypothalamus [ 69 ] , suggesting that the eff ect of ODN on food consumption is relayed by increased production of the anorexigenic POMC-derived peptide α-MSH and/or inhibition of the release of the orexigenic peptide NPY. As a matter of fact, recent data clearly demonstrate that the anorexigenic eff ect of an ODN analogue (ODN [11][12][13][14][15][16][17][18] , octadecaneuropeptide OP) is blocked by a selective antagonist of the α-MSH receptor [ 64 ] . Thus, although the AN neurons directly targeted by endozepines have not yet been identifi ed, it is actually clear that activation of α-MSH receptors is a necessary step in the anorexigenic eff ect of endozepines.…”
Section: Endozepines: Gliopeptides Involved In Hypothalamicmentioning
confidence: 98%
“…It was found that, in rats, an overnight fast markedly reduces DBI mRNA levels in cells bordering the third ventricle [ 55 , 64 ] . Central administration of glucose at the end of the fasting period partially restores DBI mRNA levels in tanycytes lining the mediane eminence and the AN, corresponding to β1 and β2 sub-populations [ 64 ] . Moreover, an increase in extracellular glucose is able to stimulate endozepine release from rat hypothalamic explants [ 64 ] .…”
Section: Endozepines: Gliopeptides Involved In Hypothalamicmentioning
confidence: 99%
See 1 more Smart Citation